Calcium modulates rapid protein phosphorylation/dephosphorylation in isolated eyespot apparatuses of the green alga Spermatozopsis similis - Linden, Lars; Kreimer, Georg (Planta, 1995)
We present an initial characterization of protein kinase and phosphatase activities associated with isolated eyespot apparatuses, the organelle involved in blue/ green-light-mediated behavioural responses of flagellate green algae. In the presence of the phosphatase inhibitors okadaic acid and vanadate, rapid overall protein phosphorylation (t(0.5) approximate to 10 s) was observed. The majority of protein kinase activities and their substrates were identified as integral or tightly-bound peripheral membrane proteins. While vanadate generally increased the phosphate incorporation into all phosphoproteins, okadaic acid specifically enhanced phosphorylation of proteins in the range of 39-43 kDa. In contrast to all other phosphoproteins in this subcellular fraction, two proteins with apparent molecular masses of 83 and 16 kDa shared remarkable similarities: (i) They exhibited a fast turnover of the P-32-label, even in the presence of phosphatase inhibitors, and (ii) their dephosphorylation was delayed at 10(-8) M free Ca2+. In addition, the 16-kDa protein underwent thiophosphorylation. The general in-vitro phosphorylation pattern was strongly influenced by alterations of free Ca2+ in a concentration range known to affect responses related to phototactic and photophobic behaviour of this alga (10(-8) M to 10(-7) M). However, characteristics of Ca2+-calmodulin-dependent protein kinases were not observed, i.e. exogenous calmodulin and trifluoperazine had no significant effect on protein phosphorylation. Also exogenous lipids (phosphatidylserine, diacylglycerol), inhibitors of cGMP- and cAMP-dependent protein kinases and protein kinase C (H-7 and HA-1004) as well as exogenously added cGMP and cAMP did not potentiate or inhibit protein phosphorylation. These characteristics of the kinase activity in our fraction most closely resemble those of the plant- and protist-specific group of Ca2+-dependent, calmodulin-independent protein kinases. In-situ phosphorylation experiments following electrophoretic separation revealed the presence of three putative Ca2+-dependent kinases or their catalytic subunits (77,48 and 47 kDa) in the eyespot preparation. In addition, a Ca2+-independent activity at 28 kDa was detected. Possible roles of reversible protein phosphorylation in eyespot apparatuses are discussed.
Keywords: CALCIUM-DEPENDENT PROTEIN PHOSPHORYLATION; EYESPOT APPARATUS; PHOTOTAXIS; PROTEIN KINASE; PROTEIN PHOSPHATASE; SPERMATOZOPSIS